2003
DOI: 10.1002/mds.10700
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal globus pallidus activity in patients with generalised dystonia

Abstract: We studied 516 globus pallidus neurons in dystonic patients. The firing rate was analysed. We classified the burst activity into tonic, burst, and pause patterns. Mean +/- SD firing rates and tonicity score for internal globus pallidus (GPi) and external globus pallidus (GPe) were 54.6 +/- 28.6; 58.01 +/- 39.1 and 1.18 +/- 0.55; 0.95 +/- 0.43, respectively. Differences in percentage appearance of tonic, burst, or paused neurons were not statistically significant for GPi versus GPe. GPi firing features in dysto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…Bursting may be oscillatory or nonoscillatory. GPi bursting in human dystonia has been reported previously (Hutchison et al 2003;Merello et al 2004;Vitek et al 1999). However, descriptions of discharge pattern are difficult to interpret in the absence of comparison data from nondystonic subjects, and only one study (Hutchison et al 2003) provided a quantitative statistical measure of bursting.…”
Section: Oscillations and Bursts In Pallidal Discharge Are Prominent mentioning
confidence: 72%
See 2 more Smart Citations
“…Bursting may be oscillatory or nonoscillatory. GPi bursting in human dystonia has been reported previously (Hutchison et al 2003;Merello et al 2004;Vitek et al 1999). However, descriptions of discharge pattern are difficult to interpret in the absence of comparison data from nondystonic subjects, and only one study (Hutchison et al 2003) provided a quantitative statistical measure of bursting.…”
Section: Oscillations and Bursts In Pallidal Discharge Are Prominent mentioning
confidence: 72%
“…A handful of studies have been published on pallidal neuronal physiology in awake humans with dystonia (23 cases total) (Hutchison et al 2003;Lenz et al 1998;Merello et al 2004;Sanghera et al 2003;Vitek et al 1999). These series focused primarily on spontaneous discharge rates.…”
Section: Comparision With Prior Studies Of Gpi Discharge Rate In Dystmentioning
confidence: 99%
See 1 more Smart Citation
“…A trend for low firing rate with a bursty pattern and oscillations was reported in the internal pallidum (112)(113)(114)(115)(116) and subthalamic nucleus (117). However, the role of anaesthesia was debated because some authors found no difference between dystonic and PD patients (118,119). The current pathophysiological model of dystonia was also questioned by data showing that pallidal DBS was able to inihibit a subpopulation of motor thalamic neurons (120) and the abscence of difference between GPe and GPi firing rate (119).…”
Section: Or Cerebellum (93)mentioning
confidence: 99%
“…However, the role of anaesthesia was debated because some authors found no difference between dystonic and PD patients (118,119). The current pathophysiological model of dystonia was also questioned by data showing that pallidal DBS was able to inihibit a subpopulation of motor thalamic neurons (120) and the abscence of difference between GPe and GPi firing rate (119). However, clear correlation between abnormal neuronal activitiy and EMG activity was reported in the basal ganglia and thalamus of patients with dystonia (116,(121)(122)(123).…”
Section: Or Cerebellum (93)mentioning
confidence: 99%